TINDAK PIDANA PELANGGARAN HAK DESAIN INDUSTRI MENURUT UNDANG-UNDANG NOMOR 31 TAHUN 2000 - Besse Sugiswati (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2004)
The violation of industrial design right has been regulated in UU no. 31/2000 and has been stated as criminal (ps.54) As it is categorized as offense that warrants complaint, there will be no law condemnation without any sue or complaint from the suffering party. As a matter of fact, this categorizing is not appropriate, as it is not fit whit the only reason of